An improved two-frequency method of capacitance measurement for SrTiO3 as high-k gate dielectric - Lue, HT; Liu, CY; Tseng, TY (My University, 2002)
An improved two-frequency method of capacitance measurement for the high-k gate dielectrics is proposed. The equivalent circuit model of the MOS capacitor including the four parameters of intrinsic capacitance, loss tangent, parasitic series inductance, and series resistance is developed. These parameters can be extracted by independently measuring the capacitor at two different frequencies. This technique is demonstrated for high-k SrTiO3 gate dielectrics and the results show that the calibrated capacitances are invariant over a wide range of frequency. In addition, the extracted loss tangent, inductance and resistance are independent on gate voltage and frequency. The effect of series resistance on the frequency dispersion of the capacitance can be also explained by this model. These results indicate that this modified technique can be incorporated in the routine capacitance-voltage (C-V) measurement procedure providing the physically meaningful data for the high-k gate dielectrics.
Keywords: MOS capacitor; capacitance measurement; frequency dispersion; STO gate dielectric